Plastic Free Market Campaign: The Effect of Message Elaboration Level on Trader’s Attitudes - Aisyah, Sri Khansa; Sarwoprasodjo, Sarwititi (Universitas Multimedia Nusantara, 2024)
Campaign is one of the strategies that can be used to change people's attitudes to be more responsible for environmental issues, especially plastic waste. The Plastic-Free Market Campaign is one of the campaigns that aims to change traders' attitudes to be wise in using single-use plastics. To determine the attitude change, the Elaboration Likelihood Model is a theory that discusses how attitudes can be formed. This study aims to analyze the correlation between the level of message elaboration and the attitude of traders toward using disposable plastic bags. This research uses a survey method and is supported by qualitative data through interviews and observations. The results showed that there is a relationship between the level of message elaboration and attitude. The lower the level of individual elaboration, the less favorable the individual's attitude towards persuasive communication messages.